Russian Montparnasse Transnational Writing in Interwar Paris - Rubins, Maria; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book reassesses the role of Russian Montparnasse writers in the articulation of transnational modernism generated by exile. Examining their production from a comparative perspective, it demonstrates that their response to urban modernity transcended the Russian master narrative and resonated with broader aesthetic trends in interwar Europe.
Keywords: European literature; Literature, Modern—20th century; Fiction; Literature—History and criticism; European Literature; Twentieth-Century Literature; Fiction; Literary History